2013
DOI: 10.1111/jhn.12152
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards and knowledge of nutrition support amongst health care professionals on London intensive care units

Abstract: The present study highlights the need for more prominent dissemination of the current guidelines and illustrates the preferred mode. Specific gaps in knowledge regarding energy intake and the use of parenteral feeding are highlighted. It is hoped that the present survey will help to guide education in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
4
8
0
2
Order By: Relevance
“…A lack of training is one of the barriers for nursing involvement in the malnutrition screening process 7 . A low level of nutrition knowledge has also been demonstrated in intensive care nurses 21 . Similar to the results of our survey of Canadian nurses caring for patients on medical and surgical wards, a survey from nurses working in general practice clinics in Australia demonstrated a need for more nutrition education 22 .…”
Section: Discussionsupporting
confidence: 76%
“…A lack of training is one of the barriers for nursing involvement in the malnutrition screening process 7 . A low level of nutrition knowledge has also been demonstrated in intensive care nurses 21 . Similar to the results of our survey of Canadian nurses caring for patients on medical and surgical wards, a survey from nurses working in general practice clinics in Australia demonstrated a need for more nutrition education 22 .…”
Section: Discussionsupporting
confidence: 76%
“…Inadequate MNT knowledge was documented among Scandinavian doctors and nurses; specifically, 25% of the 4512 professionals surveyed could not identify patients in need of MNT; 39% lacked techniques for recognizing malnourished patients; 53% found it difficult to calculate patient energy requirements; 66% were unfamiliar with national guidelines for clinical nutrition [7]. A British survey conducted among healthcare professionals working on intensive care units across London found that only 44% of the physicians and 26% of the nurses demonstrated an understanding of the evidence set out in the nutrition support guidelines [8]. Failure to identify social determinants of health as contributors to obesity together with lack of nutrition knowledge were among the barriers to treating adult obesity among US primary care physicians [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…Health professionals, in a variety of fields, have not consistently conducted translational research [3,4,5,6]. In the area of nutrition, for example, poor knowledge of medical nutrition therapy (MNT) has been reported among various medical units and teams, both in the USA and Europe [6,7,8]. Factors associated with failure to conduct successful nutritional translational research were lack of knowledge and resources [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…One study even found that physicians knew less than their patients about some dietary topics (Lazarus, 1997). Several studies have shown that nurses as well as other health professionals often have insufficient dietary knowledge (Adams et al, 2010;Lane et al, 2014;Lazarus, 1997;Mowe et al, 2008;Warber, et al, 1997;Yalcin et al, 2013). Park et al found that although most nurses are aware of the need for diet therapy, they have limited knowledge about low-cholesterol diets, sources of soluble fibre and specific foods that can help prevent disease (Park et al, 2011).…”
Section: Discussionmentioning
confidence: 99%